Challenge: Wireless Sensor Networking over White Spaces - Saifullah, Abusayeed; Lu, Chenyang; Liu, Jie; Chandra, Ranveer; Sankar, Sriram (2014)
White spaces represent unoccupied TV spectrum that could be used for wireless communication by unlicensed devices, just like Wi-Fi and ZigBee devices can use the ISM bands. This low-frequency spectrum enables high bandwidth communication at long transmission ranges. In this paper, we propose a system that leverages the benefits of white spaces for sensor networks, with a view to overcoming the limitations associated with coverage, bandwidth, time synchronization, and scalability of current wireless sensor networks (WSNs). However, the applications and requirements of WSNs pose interesting challenges for adopting white spaces. In this challenge paper, we address both the opportunities and the challenges of using white spaces for WSNs.